DERADIKALISASI PEMAHAMAN AL-QURâ€™AN: Analisis Semantik dan Konteks Historis Surah al-Fath Ayat 29 - Afrizal El Adzim Syahputra; Heru Susanto (UIN Siber Syekh Nurjati Cirebon, 2022)
Misunderstanding several verses of the Qur'an is motivated by the generalization of the understanding of the verses of the Qur'an, especially the verses related to war and jiha>d. Based on this, the writer is interested in studying Surah Al-Fath verse 29 by using semantic analysis and historical context. Based on this study, the term â€œal-shadidâ€ which is based on the term